2022
DOI: 10.3389/fonc.2022.806963
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SMAD4 Is Associated With Poor Tumor Immunogenicity and Reduced PD-L1 Expression in Pancreatic Cancer

Abstract: Transforming Growth Factor β (TGFβ) is a key mediator of immune evasion in pancreatic ductal adenocarcinoma (PDAC), and the addition of TGFβ inhibitors in select immunotherapy regimens shows early promise. Though the TGFβ target SMAD4 is deleted in approximately 55% of PDAC tumors, the effects of SMAD4 loss on tumor immunity have yet to be fully explored. Using a combination of genomic databases and PDAC specimens, we found that tumors with loss of SMAD4 have a comparatively poor T-cell infiltrate. SMAD4 loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…15 Loss of SMAD4 expression has been associated with poor survival in multiple tumour types, including pancreatic, 16 colon, 17 and oesophageal 18 cancers. Loss of SMAD4 is also associated with decreased lymphocyte infiltration of tumoral and peritumoral tissue, 19 decreased responsiveness to immune checkpoint inhibitor therapy, 20 increased resistance to 5-fluorouracil 21 and radiotherapy, 22 and increased invasion and metastasis. 23 Paiella et al found that among patients with locally-advanced pancreatic cancer treated with radiofrequency ablation, cancers with retained SMAD4 expression had a better response to treatment than cancers with loss of SMAD4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…15 Loss of SMAD4 expression has been associated with poor survival in multiple tumour types, including pancreatic, 16 colon, 17 and oesophageal 18 cancers. Loss of SMAD4 is also associated with decreased lymphocyte infiltration of tumoral and peritumoral tissue, 19 decreased responsiveness to immune checkpoint inhibitor therapy, 20 increased resistance to 5-fluorouracil 21 and radiotherapy, 22 and increased invasion and metastasis. 23 Paiella et al found that among patients with locally-advanced pancreatic cancer treated with radiofrequency ablation, cancers with retained SMAD4 expression had a better response to treatment than cancers with loss of SMAD4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al suggested that Smad4-dependent signaling in T cells makes decreases the susceptibility to spontaneous gastrointestinal tumorigenesis by maintaining homeostasis, indicating that SMAD4 signaling in T cells is required to suppress gastrointestinal cancer ( 35 ). Furthermore, Principe et al suggested that SMAD4-intact increased T cell infiltration by recruiting more T cells and therefore SMAD4 is an indicator of a survival advantage in patients with pancreatic ductal carcinoma ( 36 ). SMAD4 is required for the differentiation of CD8 + T cells during inflammatory response ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results were arranged by the Tukey method. Time-to-event survival data was evaluated via the Kaplan-Meier method [21,22]. Data were considered significant at p < 0.05 unless otherwise noted.…”
Section: Discussionmentioning
confidence: 99%